Disparities in Outcomes During Lower Respiratory Tract Infection in American Indian Children: A 9-Year Retrospective Analysis in a Rural Population in South Dakota. Issue 3 (23rd November 2021) - Palmer, Geralyn M.; Kooima, Travis R.; Van Hove, Christopher M.; Withrow, Landon L.; Gurumoorthy, Aarabhi; Lopez, Santiago M.C.
Abstract : Background: American Indian (AI) children are at increased risk for severe disease during lower respiratory tract infection (LRTI). The reasons for this increased severity are poorly understood. The objective of this study was to define the clinical presentations of LRTI and highlight the differences between AI and non-AI previously healthy patients under the age of 24 months. Methods: We performed a retrospective chart review between October 2010 and December 2019. We reviewed 1245 patient charts and 691 children met inclusion criteria for this study. Data records included demographics, clinical, laboratory data, and illness outcomes. Results: Of 691 patients, 120 were AI and 571 were non-AI. There was a significant difference in breast-feeding history (10% of AI vs. 28% of non-AI, P < 0.0001) and in secondhand smoke exposure (37% of AI vs. 21% of non-AI, P < 0.0001). AI children had increased length of hospitalization compared with non-AI children (median of 3 vs. 2 days, P < 0.001). In addition, AI children had higher rates of pediatric intensive unit admission (30%, n = 37) compared with non-AI children (11%; n = 67, P < 0.01). AI children also had higher rates (62.5%, n = 75) and duration of oxygen supplementation (median 3 days) than non-AI children (48%, n = 274, P = 0.004; median 2 days, P = 0.0002). On a multivariate analysis, AI race was an independent predictor of severe disease during LRTI. Conclusions: AI children have increased disease severity during LRTI with longer duration of hospitalization and oxygen supplementation, a higher rate of oxygen requirement and Powered by Editorial Manager and ProduXion Manager from Aries Systems Corporation pediatric intensive care unit admissions, and a greater need for mechanical ventilation. These results emphasize the need for improvement in health policies and access to health care in this vulnerable population.